Thin film fabrication of PMMA/MEH-PPV immiscible blends by corona discharge coating and its application to polymer light emitting diodes - Jung, Hee Joon; Park, Youn Jung; Choi, Sang Hun; Hong, Jae-Min; Huh, June; Cho, Jun Han; Kim, Jung Hyun; Park, Cheolmin (AMER CHEMICAL SOC, 2007)
We introduce a new and facile process, corona discharge coating (CDC), to fabricate thin polymer films of the immiscible poly[2-methoxy-5-(2'-ethylhexyloxy)-p-phenylenevinylene] (MEH-PPV) and poly(methyl methacrylate) (PMMA) blends. The method is based on utilizing directional electric flow, known as electric wind, of the charged unipolar particles generated by corona discharge between a metallic needle and a bottom plate under high electric field (5-10 kV/cm). The electric flow rapidly spreads out the polymer solution on the bottom plate and subsequently forms a smooth and flat thin film over a large area within a few seconds. The method is found to be effective for fabricating uniform thin polymer films with areas larger than approximately 30 mm(2). The thin films obtained by CDC exhibit unique microstructures where well-defined spherical and cylindrical domains of approximately 50 nm in diameter coexist. These nanosized domains are found to be much smaller than those in films made by conventional spin coating, which suggests that CDC is beneficial for fabricating phase-separated thin film structures with significantly increased interfacial areas. The effects of the applied voltage, tip-to-plate distance, and substrates on the film formation as well as the resulting microstructure are investigated. Furthermore, the light emitting performance of a device prepared by CDC is compared with one made by spin coating.
Keywords: SPINODAL DECOMPOSITION; SURFACE; MORPHOLOGY; METHACRYLATE); PERFORMANCE; DEVICES